The importance of internal communication in corporate rebranding : case study : Nors - Lencastre, Vera Andresen Guerreiro Cabral (2016)
For a corporate rebranding to be successful, it is fundamental that the employees of the company understand and support the new corporate brand from a very early stage. The aim of this thesis is to understand if the three chosen dimensions, (1) internal branding, (2) continuity of brand elements and (3) internal communication, have a positive impact on the employees’ acceptance of the new brand. A qualitative study was developed, in which the case study of the corporate rebranding of Grupo Auto Sueco to Grupo Nors was analyzed. Five semistructured interviews were conducted, with respondents from different business areas, including the holding. The results show that internal branding was important in the communication of the new message. However, for those employees who have worked longer in the company it has not been so easy to feel a connection with the new corporate brand, even though the essence of the former brand is reflected in the new brand. Internal communication was fundamental to guarantee that all employees felt involved in the building of the new brand since the beginning. In order to accomplish that, different internal communication channels were used, such as e-mail and face-to-face meetings, to invite employees to participate in workshops and interviews, where their input on the new brand was taken into account. In the final phase, tests with internal target groups were ran to analyze and study their reaction to the new brand.